Dasar-Dasar Perencanaan Beton Bertulang : Berdasarkan SKNI 1-15-1991-03 Seri 1 - VIS, W.C, KUSUMA, Gideon (Erlangga, 1994)
Dasar-Dasar Perencanaan Beton Bertulang : Berdasarkan SKNI 1-15-1991-03 Seri 1